The effect of salicylic and jasmonic acids on the activity of SnAGO genes in the fungus Stagonospora nodorum Berk. in in vitro culture and during infection of wheat plants - M. Yu. Shein; G. F. Burkhanova; I. V. Maksimov (Вавиловский журнал генетики и селекции)
RNA interference is a gene silencing mechanism that plays an important role in genetic regulation in a number of eukaryotes. Argonaute (AGO) proteins are central to the complex RNA interference system. However, their role in this mechanism, both in the host plant organism and in the pathogen, has not yet been fully elucidated. In this work, we identified and phylogenetically analyzed the SnAGO1, SnAGO2, SnAGO3, and SnAGO18 genes of the pathogenic fungus Stagonospora nodorum Berk., and analyzed their expression under conditions of infection of plants with varying degrees of resistance to the pathogen. The expression level against the background of plant immunization with the resistance inducers salicylic and jasmonic acids was assessed. In addition, the activity of these genes in the culture of the fungus in vitro was studied under the direct influence of resistance inducers on the mycelium of the fungus. Earlier activation of the SnAGO genes in in vitro culture under the influence of salicylic and jasmonic acids suggests their sensitivity to it. In an in vivo system, plant immunization to induce the accumulation of pathogen SnAGO transcripts was found. At the same time, the SnAGO genes of the fungus S. nodorum, when interacting with plant cells, reacted depending on the degree of host resistance: the highest level of transcripts in the resistant variety was observed. Thus, our data prove that the SnAGO genes of the fungus S. nodorum effectively interact with the host defense system in direct proportion to the degree of resistance of the latter to the pathogen. It was proposed to use the ratio of the transcriptional activity of the fungal reference gene SnTub to the host TaRLI gene as a marker of disease development in the initial period of the infectious process.